Implementasi Manajemen Rantai Pasok pada Industri Kue - Sir Kalifatullah Ermaya; Iwan Mulyana; Husnah Nur Laela Ermaya; Ucu Nurwati (Coopetition : Jurnal Ilmiah Manajemen, 2022)
This research is entitled "Implementation of Supply Chain Management in the Cake Industry (Case Study at Eti Snack, Kalipucang)". The writing of this research is motivated by several obstacles that are often experienced by companies. This study uses a descriptive method with a qualitative approach. The respondents consisted of the owner and five employees. The results show that: the company has implemented a supply chain management system well, suppliers are the key for the company in the sustainability of the production of various kinds of cakes, accuracy in distribution and quality of raw materials affect cake production which has implications for the quality of consumer value, and distributors act as mediators in success. the company sells products mainly for pastries. For all of this, the company is expected to continuously improve its capabilities so that it has a sustainable competitive advantage.